AKSESIBILITAS PENDIDIKAN GRATIS PADA SEKOLAH SWASTA DI GORONTALO UTARA - Ibnu Rawandhy N. Hula; Ana Mariana (Irfani, 2020)
This study aims to examine the accessibility of free education policies at senior high school of private schools in Kwandang sub-district, Gorontalo Utara districts. This type of research is a case study research, with a descriptive qualitative approach. The data sources used interviews, observations, and documentation. The results showed that the free education policy for private schools in Gorontalo Utara districts has fulfilled several aspects, namely: 1) Legal Protection, 2) Budget Sources, 3) Free Education Policy Design, 4) Implementing Organizations, 5) Free Education Costs, 6) Fund Distribution and Disbursement, 7) Accountability and Evaluation. Public accessibility to free education policies are carried out in the context of 1) stimulating equitable distribution of education in the regions, as well as providing opportunities for the less fortunate for sustainable education, 2) narrowing the space for the existence of education costs that burden students 3) encouraging private schools to compete realizing quality education, 4) providing moral and material encouragement for underprivileged children to obtain an education that was previously loaded with various types of financing items, 5) improving the quality of human resources (HR) in private schools, 6) reducing the level of children dropping out of school, ignorance, unemployment and poverty, 7) assisting students in getting the education and learning services in order to develop themselves based on their talents, interests, intelligence, and abilities, 8) assisting private schools in fulfilling adequate educational facilities and infrastructure.